Rancang Bangun Sistem Penjualan Buku Berbasis Web Dengan Metode OOAD (Studi Kasus: Toko Buku LP3ES) - Fauzi, Muhammad Iqbal; Cahyono, Yono (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2021)
LP3ES Bookstore which has been publishing books since 1972. In the process of selling books at this time it is still done offline by coming to the store and online via Instagram social media. By using a system like this, the transaction process that takes place at the LP3ES Bookstore takes a little longer to carry out the sales and reporting processes which are still done manually. So that improvements are needed to improve the quality of company services in order to ensure the convenience of transactions through system development. From the problems that occurred in the LP3ES Bookstore, the author created a web-based book sales information system using the Object Orientied Analysis and Design (OOAD) method. By applying the OOAD method in the development of the application. Information can be more easily provided to consumers, thereby increasing time efficiency in making book purchases at the LP3ES Bookstore.